Transformações Urbanas e Atividade Turística: A Experiência de Campo Grande, MS - mariani, milton pasquotto; Garcia, Daniela Sottili (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2013)
<span style="font-size: 11.0pt; line-height: 150%; font-family: "Calibri","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Arial; color: #4f6228; mso-ansi-language: PT-BR; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;">Neste artigo discutiu-se sobre as transformações urbanas em Campo Grande em decorrência do desenvolvimento da atividade turística, tendo como objetivo principal analisar a política pública de Turismo local e propor diretrizes para o desenvolvimento das mesmas. A metodologia utilizada foi a bibliográfica e documental. Contudo, buscou-se por meio desta pesquisa contribuições para discussões acerca das políticas públicas de Turismo no âmbito local, de forma a analisar, discutir e fomentar a atividade turística nesta localidade. <span style="font-size: 11.0pt; line-height: 150%; font-family: "Calibri","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Arial; color: #4f6228; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">Urban Transformations and Tourist Activity: The Experience of Campo Grande, MS<span style="font-size: 11.0pt; line-height: 150%; font-family: "Calibri","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: Arial; color: #4f6228; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US"> - In this article it has been discussed about the urban transformations in Campo Grande as result of the touristic activity’s development. It has as main goal the analysis of the public’s polices of the local tourism and proposes guidelines for the development as such. The methodology used was bibliographic and documental. However, it was searched through this research, contributions for discussions about the public’s polices of Tourism in a local scope, in a way that analyzes discusses and promotes the touristic activities in this area.